Behavior management in pediatric patients towards dentistry: Manajemen perilaku pada pasien anak terhadap tindakan kedokteran gigi - Bernadetha Lady Andita; Anie Apriani (Makassar Dental Journal PDGI Makassar, 2023)
Anxiety in pediatric patients is often found in dental practice. It is triggered by several components such as encountering unfami-liar adults, unfamiliar sounds and feelings, having to lie down for treatment, discomfort, and even pain. So that the need for be-havior management in pediatric patients in dental procedures. This case discusses the behavior management of a 6-year-old child who is accompanied by his mother and will undergo dental restoration treatment (ART). It is known that the child has a his-tory of unpleasant dental treatment and traumatizes the child in dental treatment. During the treatment process in dealing with the child's attitude, a combination of several behavior management techniques was applied such as tell-show-do, use of second lang-uage, and the presence of parents, where the application of these techniques succeeded in influencing the child's attitude which at the first appointment was negative to become positive at the second appointment and definitely positive at the third appoint-ment. It is concluded that it is important for dentists to analyze the proper technique in dealing with the behavior of pediatric patients so that dental treatment can run well and effectively.